A multicriteria methodology for maintenance planning of cycling infrastructure - Pais, Filipe (2022)
The importance of cycling as a sustainable mode has been widely recognized and, recently, its effectiveness in mitigating the spread of infectious diseases has also been under the spotlight. Fostering its use requires developing and deploying decision tools to help authorities assess the performance of their cycle infrastructure for maintenance and improvements. This article presents a multicriteria methodology based on engineering best practices and uses the ELECTRE TRI method to assign segments of the cycling network to predefined performance classes, with an aim at maintenance planning. The approach is demonstrated with a case study, which also proves scalability of the method’s data collection procedure. Case study results show that lack of safety and inadequate intersections are the main problems. These stem mostly from non-existent segregation between motorized traffic and cyclists, both along the segments and at intersections. This is typical of cities which, over the years, have prioritized motorized transportation.